Re-engineering and Technology Development on Reference Sample of Business Process (Case Study on Health Laboratory Service Company) - Vinsia Yuliana; Sugeng Santoso (Universitas Mercu Buana, 2021)
In the health laboratory companies a good service quality is the main key that should be maintained. Poor service quality would have an impact in reducing customer trust and also would have an impact on company's incomes. One of issues which happened in health laboratory companies particularly in referral sample services is inefficient times when doing the existing work which causing longer of waiting times. This research intend to identified the waste, revealed the causative factors and done the business process re-engineering which contained in reference sample of business process in health laboratory companies. This type of research were included in quantitative research with a descriptive - exploratory methods. The Data collection and analysis using primary and secondary data with quantitative data analysis. The results showed that before the business process reengineering was done, a lead time and process time needed 825 minutes, but after the repairs has done through identified the waste and determining factors which causing waste by using the BPR method, then the lead time and process time were reduced until 370 minutes, which shown there has a significant decreased amounted to 450 minutes or 54%.